Z Generation’s Expectations Against Leaders - Pierog, Anita; Erdei, Panni; Gergely, Éva (International Journal of Engineering and Management Sciences, 2016)
Expectations and ideas of labor market, workplace and leaders vary among different generations. In the current study we discuss the results of a word association survey which was conducted in 2015 among students in higher education. Students were asked to write down their first thoughts that they consider important against leaders. 391 students participated in the survey. The students formulated 20 different attribute-groups which can be classified into three main groups. Most of them defined sturdiness and empathy as their most important expectations against leaders. Attributes defined by 3-8% of respondents form the second group, while attributes defined by 1-2% are in the third group. The results show that sturdiness, confidence and authority are high above the most important skills for Generation Z.